Emerging nanoformulation strategies for phytocompounds and applications from drug delivery to phototherapy to imaging - HAN HWA SEUNG; Koo, Song Yi; Choi, Ki Young (Elsevier, 2022)
Over thousands of years, natural bioactive compounds derived from plants (bioactive phytocompounds, BPCs) have been used worldwide to address human health issues. Today, they are a significant resource for drug discovery in the development of modern medicines. Although many BPCs have promising biological activities, most of them cannot be effectively utilized in drugs for therapeutic applications because of their inherent limitations of low solubility, structural instability, short half-life, poor bioavailability, and non-specific distribution to organs. Researchers have utilized emerging nanoformulation (NF) technologies to overcome these limitations as they have demonstrated great potential to improve the solubility, stability, and pharmacokinetic and pharmacodynamic characteristics of BPCs. This review exemplifies NF strategies for resolving the issues associated with BPCs and summarizes recent advances in their preclinical and clinical applications for imaging and therapy. This review also highlights how innovative NF technologies play a leading role in next-generation BPC-based drug development for extended therapeutic applications. Finally, this review discusses the opportunities to take BPCs with meaningful clinical impact from bench to bedside and extend the patent life of BPC-based medicines with new formulations or application to new adjacent diseases beyond the primary drug indications. ？ 2021 The Authors